2015
DOI: 10.1016/j.shaw.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

A Call for Action to Improve Occupational Health and Safety in Ghana and a Critical Look at the Existing Legal Requirement and Legislation

Abstract: Occupational health and safety (OHS) is a broad field of professional practice, which involves specialists from different disciplines including but not limited to engineers, occupational health physicians, physical and biological scientists, economists, and statisticians. The preventive systems required to ensure workers are protected from injuries and illnesses dwell heavily on engineers; however, the extent to which the engineer can go regarding planning and implementing preventive measures is dependent on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 3 publications
4
46
0
Order By: Relevance
“…155) has contributed to the OHS challenges in Ghana. This development has affected the construction industry as indicated by Annan et al (2015). Kheni et al (2008) identified inadequate government support for regulatory institutions and lack of skilled human resources.…”
Section: Occupation Health and Safety Challenges In Ghanamentioning
confidence: 99%
See 4 more Smart Citations
“…155) has contributed to the OHS challenges in Ghana. This development has affected the construction industry as indicated by Annan et al (2015). Kheni et al (2008) identified inadequate government support for regulatory institutions and lack of skilled human resources.…”
Section: Occupation Health and Safety Challenges In Ghanamentioning
confidence: 99%
“…Dadzie (2013) also identified H&S training deficiency, inability to assess danger and workers reluctant attitudes towards H&S. Human resources development and inadequate OHS capacity for the industry has been indicated as some of the challenges (Puplampu and Quartey, 2012). Even though, the concept of OHS in industries was conceived in Ghana before the introduction two major edicts (Annan et al, 2015). The existence of some fragments of OHS legal requirements under jurisdictions of different agencies in Ghana has led to the OHS challenges in Ghana (Annan et al, 2015).…”
Section: Occupation Health and Safety Challenges In Ghanamentioning
confidence: 99%
See 3 more Smart Citations